Genetic Basis of Steroid Resistant Nephrotic Syndrome - Eujin Park (Korean Society of Pediatric Nephrology, 2019)
Steroid-resistant nephrotic syndrome (SRNS) has long been a challenge for clinicians due to its poor responsiveness to immunosuppressants, and rapid progression to end-stage renal disease. Identifying a monogenic cause for SRNS may lead to a better understanding of podocyte structure and function in the glomerular filtration barrier. This review focuses on genes associated with slit diaphragm, actin cytoskeleton, transcription factors, nucleus, glomerular basement membrane, mitochondria, and other proteins that affect podocyte biology.